Recent advances in additive manufacturing of Mo-Si-B alloys – A status report on the cooperative project LextrA -. Issue 1 (July 2020) - Krüger, M; Schmelzer, J; Fichtner, D; Heinze, C; Küsters, Y; Rittinghaus, S K; Weisheit, A; Heinz, R; Gerking, L; Gruber, K; Schmigalla, S; Schultze, S
Abstract: Mo-Si-B alloys are potential materials for ultra-high temperature applications, e.g. as turbine blades. Due to their excellent mechanical properties they are subject to basic research for about 20 years. The next step towards industrial application of this type of alloys is to use the current knowledge on microstructure-properties relationships and combine this with innovative laser additive manufacturing (AM). This way of processing is very challenging since the melting point of Mo-Si-B materials is > 2000 °C and the brittle-to-ductile transition temperature is typically about 900 °C. The authors demonstrate that gas atomized Mo-Si-B powders of three different compositions could be successfully processed by different AM processes, namely Direct Energy Deposition (DED) and Laser Powder Bed Fusion (LPBF). It is verified that the mechanical and oxidation properties provided by the AM materials are comparable and competitive to similar alloy compositions from conventional processes.